The Role of Greenwashing in Moderating Environmental Disclosure and Earning Response Coefficient - Novita Sari; Yunita Fitria (JASS (Journal of Accounting for Sustainable Society), 2024)
Greenwashing practices carried out by companies can make investors’ interest in responding to environmental disclosure less meaningful, because the company only creates an environmentally friendly image rather than actually minizing the operational impact on the environmental. This study aims to obtain empirical evidence about the role of greenwashing in moderating the relationship between environmental disclosure and earning response coefficient in manufacturing companies, the consumer goods subsector listed on the Indonesia Stock Exchange for the 2016-2019 period. The sampling technique used is quota sampling with 20 companies as samples. The analytical tool used in this research is Warp PLS 6.0. The results showed that environmental disclosure with earning response coefficient has a significant positive effect and greenwashing has a significant negative effect on environmental disclosure. In addition, this study also shows that the greenwashing variable can moderate the relationship between environmental disclosure and earning response coefficient.